Optimization Of Gas Turbine Performance 2.1 Using the Overhaul Combustion Inspection Method - Handoko, Susilo; Hendra, Hendra; Suharyadi, Hafid; Widiyanto, Totok (Jurnal Polimesin, 2024)
Gas turbines are one type of internal combustion drive, the initial mover utilizes gas combustion as a fluid to rotate the turbine with internal combustion. Gas turbines at private companies producing electricity use the initial movers, namely gas turbines and steam turbines. Therefore, it is also called the "Steam Gas Power Plant/PLTGU.”Private company especially in Block 2, uses two gas turbine units with Mitsubishi GT 2.1 specifications which are used as the initial drive of the generator. Types of overhauls in gas turbines are divided into three, including turbine inspection, combustor inspection, and major inspection. In maintaining the reliability of the GT 2.1 Gas Turbine, an overhaul combustion inspection was carried out in the combustion chamber because there was an increase in heat rate of 17,9% which caused a decrease in thermal efficiency and net turbine power of the GT 2.1 Gas Turbine by 17% and 2,1%. So that steps are taken to optimize the GT 2.1 Gas Turbine with the combustion inspection method by repairing and cleaning the combustion bucket nozzle. Increased thermal efficiency by 27,8% or 27,13% to 36,01% from data before overhaul. This was also followed by an increase in compressor power and turbine power so that the net turbine power increased by 38% or 141339,35 hp to 195246,54 hp.